THE IMPACT OF A STRATEGY ACCORDING TO DESIGN THINKING ON THE CREATIVE ABILITIES AND SOME BASIC VOLLEYBALL SKILLS OF MIDDLE SCHOOL STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The importance of the research lies in the use of a strategy according to design thinking to identify its impact on creative abilities and some basic skills in volleyball. Intermediate schools for boys for the first intermediate grade in the Afak District Center affiliated to the Directorate of Education of Diwaniyah for the academic year (2021 2022), whose number is (726) students representing (4) An intermediate school, and the researcher used the experimental method in the manner of the two equal groups for its suitability in applying his field procedures. As for the research sample, it included 30)) students from Maitham Al Tamar School for the first intermediate grade, which were chosen by lottery and were from the (A, B) divisions, which were selected by lottery method, Division (A ) became the experimental group and division (B) the control sample, and the necessary tools and devices were used in the research and the steps for its implementation, which included preparing a strategy according to design thinking, exploratory experience, and the main field experiment Included in the pre tests and the application of a strategy according to design thinking and then post tests the researcher concluded that the students need a strategy according to design thinking to help them develop creative abilities and some basic skills in volleyball.